A national window on critical thinking by dental educators following an ADEA webinar. Issue 5 (21st January 2021) - Krupp, Michelle M.; Holloway, Julie A.; Johnsen, David C.; Marchini, Leonardo; Butali, Azeez
Abstract: Purpose: Critical thinking is an essential skill for the dentist, yet little has surfaced to define the outcome, guide learning, and assess performance. On June 16, 2020, the American Dental Education Association (ADEA) sponsored a 1‐hour webinar on Critical thinking with 600 attendees. To report input from a national cohort of dental educators responding to a model for critical thinking guidance. Methods: Critical thinking concepts with explicit skillsets were presented. Attendees gave Likert responses on importance and confidence defining outcome. At the end of the webinar, attendees were asked in an open‐ended format what their "take away" was. Results: One hundred and five responded to a Likert scale question on how important critical thinking is, with 93% giving a 5. To the question on how well have you figured out how to define the outcome, guide learning, and assess performance, 53% gave a 3 and 21% gave a 2 (χ 2 = 151; P < 0.01) From 121 "take away" responses, 79 reiterated the session's central theme with comments on emulating the thought process of the expert or articulating a skillset. In a separate classification of the same "take away, " responses oriented to common domains of education nomenclature. No alternative critical thinking model for articulating the outcome, guiding learning, and assessing performance was evident in any of the 121 take away responses. Conclusions: Results are interpreted as an opportunity moment for dental education to collectively develop additional critical thinking models.